Periductal Stromal Tumor of the Breast: A Case Report and Review of the Literature - KAYA, HANDAN (AVES, 2016)
We present a woman aged 50 years who underwent a Tru-cut biopsy for a BI-RADS 4 lesion on her right breast and received a histopathology diagnosis of a fibroadenoma. In her one year follow-up, the lesion had progressed and she underwent an excisional biopsy. Her final diagnosis was a periductal stromal tumor. Periductal stromal tumor is an extremely rare and different entity from phylloides tumor, which makes appropriate diagnosis difficult in Tru-cut biopsy and care should be taken. Lesion progression of should require a re-biopsy. Their tendency to recur warrants follow-up. We believe that radiologic, pathologic, and clinical correlation is key in decision-making and diagnosis of these tumors.
Keywords: Breast neoplasm; periductal stromal tumor; ultrasound; mammography; SARCOMA; DIAGNOSIS; CELLS